-(r+7)+1=-3(-8r+2)

Simple and best practice solution for -(r+7)+1=-3(-8r+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(r+7)+1=-3(-8r+2) equation:


Simplifying
-1(r + 7) + 1 = -3(-8r + 2)

Reorder the terms:
-1(7 + r) + 1 = -3(-8r + 2)
(7 * -1 + r * -1) + 1 = -3(-8r + 2)
(-7 + -1r) + 1 = -3(-8r + 2)

Reorder the terms:
-7 + 1 + -1r = -3(-8r + 2)

Combine like terms: -7 + 1 = -6
-6 + -1r = -3(-8r + 2)

Reorder the terms:
-6 + -1r = -3(2 + -8r)
-6 + -1r = (2 * -3 + -8r * -3)
-6 + -1r = (-6 + 24r)

Add '6' to each side of the equation.
-6 + 6 + -1r = -6 + 6 + 24r

Combine like terms: -6 + 6 = 0
0 + -1r = -6 + 6 + 24r
-1r = -6 + 6 + 24r

Combine like terms: -6 + 6 = 0
-1r = 0 + 24r
-1r = 24r

Solving
-1r = 24r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-24r' to each side of the equation.
-1r + -24r = 24r + -24r

Combine like terms: -1r + -24r = -25r
-25r = 24r + -24r

Combine like terms: 24r + -24r = 0
-25r = 0

Divide each side by '-25'.
r = 0

Simplifying
r = 0

See similar equations:

| 10(2x+4)=-1(-8-9x)+3 | | 2x-(3x+4)= | | x^2-2=18 | | 2mn= | | .7z+1.9+.1z=5.5-.42 | | 7x-65=43-2x | | -4(6x)= | | 5x+3(6x+15)=160 | | .0825t^2-.0924t+1.784=0 | | -12x=144 | | 1.2x+1.1=7.7-x | | 48=8 | | 18(x-1)+x=12-11x | | 3.75+7=8.1b-19.4 | | 3x+5-4x=7 | | (T-4)(t+1)=0 | | -17+3x=5x+7 | | 12w+w=5-2w | | 18+2y=4y-8 | | -2x-70=29+9x | | 3(a+7)=-6 | | 7x+5x-80=136 | | 5=3x-13 | | 7y-9(5y-5)= | | 6x^2=13x-6 | | (x)+(x+2)=23 | | (M+3)-2m=3(m-3) | | 5x+67=180 | | 25x^2+30x=-9 | | 4(-4x+4)=208 | | -2x^3y+4x^2y^2+70xy^3=0 | | -15-(-2)-(11-6)= |

Equations solver categories